Student bystander behavior and cultural issues in cyberbullying: when actions speak louder than words - Costa Ferreira, P. A. N. (2016)
This study aims to investigate whether student bystander interventions can influence the relationship between being a bystander of a cyberbullying incident and being the victim or the aggressor. Another aim is to understand the specific behavior presented by students bystanders, namely whether they noticed incidents of cyberbullying and interpreted these events as an emergency and which actions they determined as being appropriate in providing assistance. Following a cross-cultural perspective to reach these aims, a total of 788 Portuguese and Brazilian college students answered to the Cyberbullying Inventory for College Students. Moderation analysis revealed that intervening moderated the relationship between being the bystander of cyberbullying and being the victim and/or aggressor. A three-way interaction showed that this relationship was stronger in Brazilian students, revealing that the bystanders who were inactive were more likely to also become a victim or an aggressor themselves, whereas those who intervened were less likely to become a victim or an aggressor. Implications for future research and interventive action are discussed.